Kenneth Arrow's Last Theorem - Paul Milgrom (Journal of Mechanism and Institution Design)

(untitled)
In Kenneth Arrow's last week of life at age 95, he reported that "I began my research career with an impossibility theorem. If I had time now, my last theorem would be an impossibility theorem about social choice for environmental policy." This paper completes the formalization, proof, and discussion of the theorem that Arrow then described.